Pengaruh Upah dan Insentif terhadap Kepuasan Kerja pada UD. Barokah Desa Paokmotong - Yohana Safitri; Luluk Fadliyanti; Vici Handalusia Husni (Postgraduate, University of Mataram, 2026)
This study aims to analyze the effect of wages and incentives on employee job satisfaction at UD. Barokah Desa Paokmotong. The research method used a quantitative approach with an associative type of research. The research sample included all employees of UD. Barokah, totaling 35 respondents. Primary data were obtained through questionnaires using a Likert scale and analyzed with ordinal logistic regression tests using Stata. The results of the study indicate that wages and incentives have a positive and significant effect on job satisfaction both simultaneously and partially. The research model is deemed feasible with a LR Chi-square value of 44.88 and a p-value of 0.0000, as well as a McFadden R2 value of 0.5039, indicating that variations in job satisfaction can be explained by these two compensation variables. This study emphasizes that financial compensation is a dominant factor in improving job satisfaction in small businesses such as UD. Barokah in Paokmotong Village.